2021
DOI: 10.1136/tsaco-2021-000773
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating the Tactical Combat Casualty Care principles in civilian and military settings: systematic review, knowledge gap analysis and recommendations for future research

Abstract: ObjectivesThe Tactical Combat Casualty Care (TCCC) guidelines detail resuscitation practices in prehospital and austere environments. We sought to review the content and quality of the current TCCC and civilian prehospital literature and characterize knowledge gaps to offer recommendations for future research.MethodsMEDLINE, EMBASE, CINAHL, and Cochrane Central Register of Controlled Trials were searched for studies assessing intervention techniques and devices used in civilian and military prehospital setting… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0
4

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 125 publications
(277 reference statements)
0
4
0
4
Order By: Relevance
“…An inflation of a cuff with cold air will cause high cuff pressures with risk of rupture because the inflated air will warm and expand and cold tubes may cause FCI at the point of contact [ 18 , 21 ]. Freezing of condensation water may cause equipment dysfunction and tube/heat moisture filter obstruction [ 22 , 35 ]. If the patient is not in respiratory distress, a cold air mask or, if not available, a scarf should be placed over the external airway, to better pre-warm the inhaled air.…”
Section: Discussionmentioning
confidence: 99%
“…An inflation of a cuff with cold air will cause high cuff pressures with risk of rupture because the inflated air will warm and expand and cold tubes may cause FCI at the point of contact [ 18 , 21 ]. Freezing of condensation water may cause equipment dysfunction and tube/heat moisture filter obstruction [ 22 , 35 ]. If the patient is not in respiratory distress, a cold air mask or, if not available, a scarf should be placed over the external airway, to better pre-warm the inhaled air.…”
Section: Discussionmentioning
confidence: 99%
“…[61][62][63] Nevertheless, conclusive evidence remains weak. 24,64 In terms of safety, tourniquets have remained a controversial topic because of their complications, which are primarily related to ischemia and compression. 65,66 Reviews of recent combat and civilian experiences have shown minimal morbidity, but the total tourniquet time in these studies was less than 2 h in most of the casualties.…”
Section: Cardiovascular Deconditioning and Hematological Changesmentioning
confidence: 99%
“…11 Both XStat and iTClamp may be particularly useful in space as they are small and require minimal training to us, but for both devices, efficacy and safety in prehospital and austere environments—including space—remain to be determined. 64…”
Section: External Hemorrhage Control In Spacementioning
confidence: 99%
“…Наступний крок протоколу «MARCH» (Respiration) передбачає особливий акцент на важливості оцінки дихання постраждалого у випадку поранення грудної клітки, з ймовірним формуванням напруженого пневмотораксу [7]. За даними R. «Art of Medicine» тільки дихальної недостатності, але й шокового стану та зупинки серця потерпілого [8]. Хоча питання виникнення пневмотораксу та його усунення не є базовим в практиці отоларинголога й не входить до навчальної програми для лікарів-інтернів отоларингологів, оволодіння навиком голкової декомпресії грудної клітки у випадку напруженого пневмотораксу, накладання оклюзійної пов'язки на рану викликало особливу зацікавленість у здобувачів післядипломної освіти в рамках вивчення принципів TCCC.…”
Section: рис 4 лікарі-інтерни проводять зупинку вузлової кровотечі з ...unclassified